Uji penghambatan enzim α-glukosidase ekstrak etanol daun karas tulang (Chlorantus erectus) - Arly Syahputri , Janies; Haryoto, Haryoto (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Karas tulang plant (Chloranthus erectus) is a medicinal plant that has been used in several areas such as China and Southeast Asia. There has been no research regarding the potential of bone karas leaves as an antidiabetic through inhibiting the α-glucosidase enzyme from the ethanol extract of bone karas leaves. Inhibition of the α-glucosidase enzyme can work due to the presence of phytochemical compounds, such as flavonoids, saponins, tannins and quinones. This is because the phytochemical compounds contained therein can act as antidiabetic agents to prevent hyperglycemia in diabetes sufferers. This research aims to identify chemical compounds and the activity of the α-glucosidase enzyme in the ethanol extract of leaves contained in karas bone leaves. The thin layer chromatography method was used to screen phytochemical chemicals for alkaloids, flavonoids, saponins and tannins. The ELISA reader 405 nm method was used to test the inhibition of the α-glucosidase enzyme. The substrate used was p-NPG while the comparison used was acarbose tablets. The results of this research were that the IC50 value for the extract was 30.541 ????g/mL while for acarbose it was 3.873 ????g/mL. From these results it can be concluded that the inhibitory power of the α-glucosidase enzyme is in the active category, while that of acarbose is in the very active category.